1978
DOI: 10.1073/pnas.75.3.1242
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian oocyte maturation and protein synthesis: Related inhibition by cyclic AMP, theophylline, and papaverine

Abstract: Two inhibitors of cyclic AMP phosphodiesterase (3':5'-cyclic-AMP 5'-nucleotidohydrolase, EC 3.1.4.17), theophylline and papaverine, inhibit the maturation of Xenopus laevis oocytes induced by four different stimuli: human chorionic gonadotropin, progesterone, testosterone, and lanthanum ions. Addition of 1 mM cyclic AMP to the medium delays maturation by approximately 2 hr. Papaverine, theophylline, and cyclic AMP inhibit amino acid incorporation into oocyte proteins by 50% or more but do not inhibit amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 23 publications
5
18
0
Order By: Relevance
“…Although cAMP levels show a partial, transient drop soon after progesterone addition and another drop before GVBD (15,18,54,55), total cellular PKA activity shows only minor fluctuations in activity between progesterone addition and GVBD (data not shown). Taken together, these results suggest that the phosphorylation status of cdc25 on Ser-287 could be controlled by selective, compartmentalized binding of cdc25, PKA, and the Ser-287 phosphatase to one of the substrate-specific PKA scaffolding proteins known as AKAPs (56,57).…”
Section: Resultsmentioning
confidence: 99%
“…Although cAMP levels show a partial, transient drop soon after progesterone addition and another drop before GVBD (15,18,54,55), total cellular PKA activity shows only minor fluctuations in activity between progesterone addition and GVBD (data not shown). Taken together, these results suggest that the phosphorylation status of cdc25 on Ser-287 could be controlled by selective, compartmentalized binding of cdc25, PKA, and the Ser-287 phosphatase to one of the substrate-specific PKA scaffolding proteins known as AKAPs (56,57).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, there appears to be a consensus that progesterone causes a rapid (within minutes) but modest (~20%) reduction of cAMP (Smith, 1989). However, some have also reported that this reduction is transient, with levels of cAMP recovered quickly (within 10-20 minutes) , whereas others have reported more persistently reduced levels of cAMP throughout the maturation process (Bravo et al, 1978). The basal cAMP concentration in G2 oocytes is estimated as 1 pmol/oocyte ) (V. Montplaisir and X. J. Liu, unpublished data) or 1 µM (assuming 1 µl as the average volume of a sphere of 1.2-1.3 mm diameter).…”
Section: Discussionmentioning
confidence: 99%
“…In Xenopus, progesterone-induced oocyte maturation is associated with a rapid transient decline (20-60%) in cAMP (Maller et al, 1979;Cicirelli and Smith, 1985), due to inhibition of adenylate cyclase (AC) (Sadler and Maller, 1981;Sadler and Maller, 1985;Finidori-Lepicard et al, 1981). Furthermore, interventions that increase cAMP, either through activation of AC (Schorderet-Slatkine and Baulieu, 1982), increasing protein kinase A (PKA) activity (Maller and Krebs, 1977) or inhibiting cAMP phosphodiesterase (Bravo et al, 1978;Sadler and Maller, 1987), block progesteroneinduced oocyte maturation. Supporting these results, inhibition of PKA induces oocyte maturation in the absence of progesterone (Maller and Krebs, 1977;Huchon et al, 1981;Sun and Machaca, 2004;Daar et al, 1993).…”
Section: Introductionmentioning
confidence: 99%